2012
DOI: 10.1016/j.sna.2011.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and experimentation of a passive low frequency nanoforce sensor based on diamagnetic levitation

Abstract: To cite this version:Joël Abadie, Emmanuel Piat, Stéphane Oster, Mehdi Boukallel. Modeling and experimentation of a passive low frequency nanoforce sensor based on diamagnetic levitation.. Sensors and Actuators A: Physical , Elsevier, 2012, 173, pp.227-237. 10.1016/j.sna.2011 Modeling and experimentation of a passive low frequency nanoforce sensor based on diamagnetic levitation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 30 publications
0
40
0
Order By: Relevance
“…As a result, a new generation of micro-sensors and actuators based on levitation have been demonstrated, covering a wide range of applications, e.g., as microinertial sensors [1]- [4], frictionless micro-bearings [5], [6], bistable switches [7], micro-accelerator [8], linear-micro-actuator [9], and nano-force sensor [10]. We will generally refer to all these devices as contactless suspensions (CS).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, a new generation of micro-sensors and actuators based on levitation have been demonstrated, covering a wide range of applications, e.g., as microinertial sensors [1]- [4], frictionless micro-bearings [5], [6], bistable switches [7], micro-accelerator [8], linear-micro-actuator [9], and nano-force sensor [10]. We will generally refer to all these devices as contactless suspensions (CS).…”
Section: Introductionmentioning
confidence: 99%
“…To perform these tasks, new instrumentation compatible with ART constraints and physicians' habits is necessary. With their low stiffness and their high ranges of force measurement, force sensors based on magnetic springs [23,24,25] could be a potential solution to design such instrumentation.…”
Section: Introductionmentioning
confidence: 99%
“…The magnet had an outer diameter of 3.175 mm and inner diameter of 1.588 mm [69,70]. The application of DLMA in nanoforce sensors was studied theoretically and experimentally by Abadie et al in [71], where the authors demonstrated a prototype of their sensor with a bandwidth of 4 Hz and a resolution of 5 nN.…”
Section: Diamagnetic Levitation Micro-actuatorsmentioning
confidence: 99%